Pengawasan Dewan Perwakilan Rakyat Daerah Terhadap Anggaran Pendapatan dan Belanja Daerah di Indonesia - Mhd Ansori; Nuraini Nuraini (Wajah Hukum, 2021)
The Regional People's Representative Council (DPRD) as a regional people's representative institution as well as an element of regional government administration that functions as a supervisor, however, has not run optimally the supervisory function of the DPRD so that the mission and goals set by the regional government can be achieved. The relationship between the executive and the legislature tends to be “troublesome”, these two institutions often do not understand their respective powers and functions. In order to carry out its functions, one of which is carried out by the DPRD by carrying out supervision, supervision by the DPRD on the administration of government is very important to maintain effective and efficient development and harmony in the implementation of government tasks. There has been an overlapping authority related to the supervision of the Regional Revenue and Expenditure Budget (APBD), and it is not even clear how DPRD members supervise the APBD, this makes DPRD members not optimal in carrying out supervision. The purpose of this paper is to find out and analyze the DPRD's oversight of the APBD, so this type of research is normative juridical research, meaning research that focuses on examining the application of positive legal norms and rules. The approach used in this research is conceptual, legal approach and historical approach.